O uso de tecnologias da inteligência para a gestão da demanda de produtos no ciberespaço: estudo de caso "Captare" - Figueiredo, Karen Patrícia Reis (2009)
The thesis entitled "The Use of Technologies of Intelligence on Demand Management of Cyberspace Products: Case Study 'Captare'", of the Master in Technologies of Intelligence and Digital Design - TIDD, focuses on how the industrial segments can come to know and understand, in a more effective way, the behavior of demand in retail. It was analyzed how intelligence softwares with a cognitive basis can collect, process, classify and interpret data generated from business to business transactions B2B. As a main informational means to be examined, within the case methodological line, it proposes the Captare Software used by industrial segments through an eMarketplace (Genexis.com). Captare is a information product (e-Business solution) supported by technology of algorithm intelligence in cyberspace with cognitive representation pattern. Its conception is based on the hybrid convergence of the multidisciplinarity of statistics, data mining, marketing, trade marketing, technology of information and hypermap, promoting interactive communication strategies of the triad "man", "interface" and "computer", turning it into a set to make the objectives happen, such as action, reaction, service or information